1937
DOI: 10.1017/s0022029900001941
|View full text |Cite
|
Sign up to set email alerts
|

152. Studies on the chemistry of Cheddar cheese making. V. Factors influencing the acidity and mineral content of cheese

Abstract: It has been shown that the acidity developed in a vat of milk at the “running” stage has a very important influence on the quality of the resultant cheese. A high acidity causes increased mineral losses in the whey and a corresponding lowering of the mineral content of the cheese, while it also has a detrimental effect on the body of the cheese. The acidity at “running” also controls to a great extent the acidity of the cheese produced. Even where the acidities at the late stages of the process are kept the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

1938
1938
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 3 publications
4
12
0
Order By: Relevance
“…The pH is expected to increase during ripening because of the neutralizing effect of alkaline products of protein degradation (Webb et al, 1974). The pH values were similar to values reported in the literature for traditional Cheddar cheese, which ranges from 4.80 to 5.29 after 1 day and 5.40 to 5.60 after 60 days of ripening (Dolby et al, 1937;Czulak et al, 1969). The pH values of UF Cheddar cheese were reported to range from 5.40 to 5.97 (Green et al, 1981;Sutherland and Jameson, 1981).…”
Section: Change Of Ph During Ripeningsupporting
confidence: 83%
See 2 more Smart Citations
“…The pH is expected to increase during ripening because of the neutralizing effect of alkaline products of protein degradation (Webb et al, 1974). The pH values were similar to values reported in the literature for traditional Cheddar cheese, which ranges from 4.80 to 5.29 after 1 day and 5.40 to 5.60 after 60 days of ripening (Dolby et al, 1937;Czulak et al, 1969). The pH values of UF Cheddar cheese were reported to range from 5.40 to 5.97 (Green et al, 1981;Sutherland and Jameson, 1981).…”
Section: Change Of Ph During Ripeningsupporting
confidence: 83%
“…Cheese with high lactose at the time of hooping may develop low pH while maturing (Dolby et al, 1937) and may have a greater risk in off-flavor development due to nonstarter bacteira (Lawrence and Gilles, 1982). However, this was not observed in this experiment, probably because the high buffer capacity of UF cheese neutralized the effect as described by Huffman and Kristoffersen (1984).…”
Section: Degradation Of Lactose During Ripeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Minor changes in the manufacturing protocols during natural cheese manufacture, such as set pH, drain pH, and level of salting (salt‐to‐moisture ratio), can significantly change the state and amount of calcium and phosphorus in natural cheese (Dolby and others 1937; Czulak and others 1969; Upreti and Metzger 2006). In a study on low‐fat mozzarella cheese, Metzger and others (2000) studied the effect of cheese milk set pH on the amount and state of calcium in the final cheese.…”
mentioning
confidence: 99%
“…Dolby et al (167), continuing their studies on Cheddar cheese-making, have found that the acidity of whey at running influences the mineral content and the body of cheese. The acidity of cheese is dependent on the acidity of the whey at running and the amount of lactose remaining in the curd.…”
Section: Milk Products (A) Buttermentioning
confidence: 96%